P188 MANAGEMENT OF ANTICOAGULANT AND ANTIPLATELET THERAPY IN THE GREAT ELDERLY: A REAL LIFE CLINICAL CASE. (18th May 2022) - Prenna, E; Maffè, S; Facchini, E; Bergamasco, L; Paffoni, P; Careri, G; Franchetti Pardo, N; Paino, A; Dellavesa, P
Abstract: In daily clinical practice we have often to manage great elderly people with multiple comorbidities. In these cases it is not always easy to apply the guidelines, which must sometimes be adapted to the patient we are treating. We present the case of a 99–year–old hypertensive patient in therapy with oncocarbide and acetylsalicylic acid for polycythemia vera. No cardiological history. It came to our attention for NSTEMI during an episode of persistent atrial fibrillation (AF) with a high ventricular rate. Subsequent spontaneous restoration of sinus rhythm. Significant increase in troponin on blood tests. On the echocardiogram, normal biventricular kinetics and systolic function, no significant valvulopathies. Given the age and hemodynamic stability, a conservative approach was chosen. Therefore, antiplatelet therapy was started with acetylsalicylic acid (ASA) and anticoagulant therapy, initially with low molecular weight heparin and then with oral anticoagulant (NOAC); being the patient over 75 we chose Apixaban 2.5 mg bid, in accordance with weight and renal function (Consensus ESC 2016). At 1 month follow up the patient month was stable in good compensation, the 24h–Holter ECG showed stable sinus rhythm. At this point the question was how to proceed with the therapy: maintain the NOAC, as indicated in the NSTEMI guidelines, or continue with ASA alone, also considering that the risk scores usually used in patients with AF to determine the bleeding and cardioembolic risk (HASBLED and CHADS–VASC) are not validated in such elderly patients. We also hypothesized that the short AF paroxysm was related to ongoing myocardial ischemia (and not vice versa); in the literature, however, the indication for anticoagulant therapy does not take these extreme situations into account. Polycythemia vera also contributes to complicating the situation, exposing the patient to an increased risk of thrombotic events in the absence of antiplatelet therapy. After discussing the case with the haematologist, we decided to suspend the NOAC, also considering the absence of new arrhythmic episodes, and to continue with ASA alone. For now, with a follow–up of 6 months, we have not registered thrombotic / haemorrhagic problems or arrhythmic recurrences. The management of the elderly is always complex and will frequently lead us to adapt and customize the treatments on every single patient.